The Influence of Perceived Convenience, Perceived Usefulness, Trust, Word of Mouth on Customer Satisfaction Case Studies on Shopee Users - Nuria Maspiana Siregar; Zulkarnain Nasution; Fauziah Hanum (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
In today's modern era, buying and selling is not only done face to face, but can be done without face to face, namely through applications that can be operated via mobile phones. In Indonesia, the most well-known buying and selling platform is Shopee. At Shopee, sellers and buyers can make transactions without the need to meet face to face, plus many facilities that make it easier for consumers to choose the right item and also very complete payment facilities. In this study, researchers wanted to analyze the factors that can foster consumer satisfaction after making purchases on the Shopee application. Based on a literature study conducted by researchers, obtained variables that are thought to have a direct influence on customer satisfaction when making purchases on the shopee application. The variables are perceived convenience, perceived usefulness, trust and word of mouth. Based on this, the researcher wants to test the direct impact of these variables. The research uses a quantitative approach with data analysis using the SPSS26 application, data is collected through a Google form which is shared online. The results of the study show that all predictor variables have a positive and significant influence on customer satisfaction when shopping at the Shopee application.